Tingkat Pemahaman Guru PJOK Terhdap Pembelajaran Blended Learning Pada Tingkat SMA/SMK se-Kecamatan Setu - Haryanto Haryanto; Abdul Salam; Ruslan Abdul Gani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is motivated because in its implementation there are still PJOK teachers who do not take serious handling of the blended learning learning method, even PJOK teachers only do learning without thinking about what method to use. This study aims to determine how big the level of understanding of PJOK teachers towards blended learning. This research is a quantitative descriptive research, the method used is a survey. The data collection technique was in the form of a questionnaire using a test question with a choice of true or false answers. The population used is PJOK SMA/SMK teachers in Setu District, totaling 28 teachers. The sample used in this study is the total of the population in the study. The data in the study were analyzed using descriptive statistics with percentages. The results showed that the level of knowledge of PJOK teachers on blended learning at the SMA/SMK level in Setu District was in the medium category with 12 teachers and a presentation of 43%.